2010
DOI: 10.1111/j.1365-2559.2010.03640.x
|View full text |Cite
|
Sign up to set email alerts
|

YKL‐40 and mast cells are associated with detrusor fibrosis in patients diagnosed with bladder pain syndrome/interstitial cystitis according to the 2008 criteria of the European Society for the Study of Interstitial Cystitis

Abstract: Serum and urine levels of YKL-40 may be used as non-invasive biomarkers in BPS/IC for the evaluation of bladder fibrogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 54 publications
2
44
0
1
Order By: Relevance
“…Bladder fibrosis is related to the considerable reorganization of the collagen contents in the ECM, and its pathological mechanism may be different owing to the various causes of the fibrosis [7]. Bladder pain syndrome or interstitial cystitis may result in detrusor fibrosis [8]. MicroRNAs (miRNAs) might regulate disease development by influencing the production of cystic fibrosis transmembrane conductance regulator (CFTR) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Bladder fibrosis is related to the considerable reorganization of the collagen contents in the ECM, and its pathological mechanism may be different owing to the various causes of the fibrosis [7]. Bladder pain syndrome or interstitial cystitis may result in detrusor fibrosis [8]. MicroRNAs (miRNAs) might regulate disease development by influencing the production of cystic fibrosis transmembrane conductance regulator (CFTR) [9].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical studies have shown an increased levels of mast cell mediators including histamine (elMansoury et al 1994), tryptase (Boucher et al 1995 and IL-6 (Erickson et al 1997) in the urine. Furthermore, the serum and urine levels of a new biomarker YKL-40, which is expressed in bladder mast cells, can be evaluated as an inflammatory mediator of bladder fibrogenesis in patients (Richter et al 2010). The critical role of neural-immune interactions in pathogenesis of interstitial cystitis has been documented.…”
Section: Bladder Pain Syndrome (Interstitial Cystitis)mentioning
confidence: 99%
“…S1C). It is reported that IC is associated with fibrosis of layers of the bladder wall [36]. Thus, we performed Masson's trichrome staining of the bladder tissues in each group.…”
Section: Histo-and Immunohistochemical Analysesmentioning
confidence: 99%